Analysing Land-use Land Cover (LULC) and Development Change in Nearby University Campuses’ Area: A Case of Universiti Teknologi MARA Negeri Sembilan, Malaysia - Mohd Zain, Wahidah; Idris, Sufy Rabea Adawiya; Mohd Ramsi, Mohd Faizal; Nordin, Siti Khairiyah (Journal of Science and Technology, 2021)
After 20 years of establishment, the number of Universiti Teknologi MARA (UiTM) campuses across Malaysia has reached 35 in number. Although the campuses’ development of campuses had somehow made the location widely known as one of the education hubs in Malaysia, there exist doubts about the extent of development of each campus in an area that can benefit the locality. The focus of this paper is assessing the land-use changes due to the development of three campuses of UiTM Negeri Sembilan from 1999 to 2019. This study uses satellite images, GIS technology, and web-based maps applications as data collection tools. Two aspects were assessed, viz; Land-use Land Cover (LULC) and change detection. The result shows an increasing pattern of LULC. Also, the land conversion occurred more in Seremban compared to UiTM Kuala Pilah and Rembau. Change detection analysis in this paper reveals that the green area is declining via a higher percentage of deforestation and urbanization. Land-use change detection technique is confirmed as an effective method for measuring and evaluating urban development operations and their effect. Therefore, this research emphasized that LULC and change detection analysis results beneficial in identifying the development impact and important to facilitate strategize steps and policies in averting the affected areas from pollution and deforestation side effects. This study also suggests that such research extended to more Institutes of Higher Learning in Malaysia and South East Asia. The findings should be valuable to researchers, town planners, university administrators, and local authorities alike and contribute towards sustainable land-use planning and management in Malaysia in the near future.